The Canaanite Woman, the Second Nun, and St. Cecilia - Dobbs, Elizabeth A. (Christianity & literature, 2013)
Chaucer’s little-noticed allusion to the story of the Canaanite woman in his Prologue to the Second Nun’s Tale brings several aspects of his poem into focus. What he gains by alluding to this account can be seen in a comparison of its source text, Matt. 15:21-28, to the very different version of this story in Mark 7:24-30. In particular, the allusion emphasizes the characterization of the Second Nun and St. Cecilia as speakers, underlines the saints conversions as the radical results of her rhetorical skill, and reinforces a theme of dissolving boundaries.